Rulings of time in the Holy Quran (acts of worship as a model) - Sami, Yaqdgan; Jassim Haloub, Khudair (International Journal of Psychosocial Rehabilitation, 2020)
Islamic law has attached particular importance to the time of Lotta upholstering accept worship and whether or not, and that time equivalents and have the meanings of the asymptotic time, or are the same time, and that a clear time effect Balebadat, in terms of acceptance and whether or not Vasalap linked close association must be authorized time, the month of fasting imposed worship By it and not exceeding it , and the time shall determine its effect on the obligation of the obligation of zakat, and the Hajj has a number of days , and the pilgrimage does not take place except with it.